Pattern of Dental Problems among Patients Visiting a Dental Hospital during COVID-19 Pandemic - Dixit, P.B.; Dixit, S.; Dahal, S.; Poudel, P.; Roy, D.; Manandhar, N. (Kathmandu University Medical Journal, 2020)
Background Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Nepal is a part of this worldwide corona virus disease. In this critical situation, the patients have a sense of insecurity visiting dental hospital. Objective To assess the pattern of dental problems in patients visiting a dental college during COVID-19. Method A descriptive cross-sectional study was conducted in Dental Hospital of Kathmandu Medical College and Teaching Hospital from May to August 2020. The patients visiting the Dental hospital were assessed for dental problems. Data were analyzed in Statistical Package of Social Sciences version 20. Frequency and percentage for pattern of dental problems were calculated. Result Most of the patients of age group of 14 to 31 years 530 (36.53%) had dental problems during the survey period. Out of total patients having dental emergency, 739 (50.93%) were males and 712 (49.07%) were females. Majority 545 (37.56%) visited the dental hospital for endodontic consultation followed by emergency consultation for oral surgical procedures 298 (20.54%). Least consulted dental emergency condition was prosthodontic consultation 18 (1.24%). Conclusion The study findings showed that the major dental problems in patients causing emergency visit to dental hospital during COVID-19 pandemic period were dental pain and swelling requiring endodontic consultation and the least need felt is prosthodontic consultation.